Explaining the brain mechanisms and the mosaic unity of neuroscience - Craver, Carl F. (Oxford : Clarendon, 2007)
Craver offers explicit standards for successful explanation of the workings of the brain, on the basis of a systematic view about what neuroscientific explanations are: they are descriptions of mechanisms.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Neurosciences -- Philosophy; Brain -- Philosophy